Optimalisasi Software Mendeley dalam Peningkatan Kualitas artikel ilmiah bagi Mahasiswa Fakultas Ilmu Keolahragaan Universitas Cenderawasih - Ansar CS; Abd Rahman Yus (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Mendeley is a reference management software that provides various features to assist students in the process of writing scientific articles. This engagement method is carried out through a series of activities, including workshops, training, and mentoring. The purpose of this engagement is to improve the skills of final semester students in compiling scientific articles. The activity was held in May 2023 with participants from FIK UNCEN semester 7 students. The results showed that students were able to operate the Mendeley application, starting from registering an account on the Mendeley web and installing the Mendeley desktop application, and using the Mendeley application to create automatic citations/references and bibliographies. The conclusion is that FIK UNCEN students are able to use the Mendeley application to improve their academic writing skills effectively and correctly